Efficacy and safety of omadacycline for the treatment of infectious diseases: a real-world, retrospective study of 2587 patients - Liu, Jian; Liu, Jiayi; Li, Huangyi; Pang, Jiali; Chen, Siyun; Liu, Jianming; Ouyang, Aijun (Frontiers in Pharmacology, 2025)
ObjectivePrevious randomized controlled trials have shown good efficacy and safety of omadacycline in patients with infectious diseases, but relevant real-world evidence is still insufficient. This large-scale study aimed to explore the efficacy and safety of omadacycline for the treatment of infectious diseases in real-world conditions.MethodsThis was a retrospective, real-world study. A total of 2587 patients with infectious diseases who received omadacycline treatment were enrolled. Clinical success was defined as resolution or significant improvement of infection-related signs and symptoms without the need for salvage antimicrobial therapy.ResultsAfter omadacycline treatment, 81.6% of patients achieved clinical success. Multivariate logistic regression analysis suggested that older age [odds ratio (OR): 0.991, P = 0.025], history of any malignancy (OR: 0.630, P = 0.016), abnormal renal function (OR: 0.432, P = 0.003), mechanical ventilation (OR: 0.559, P = 0.013), intensive care unit (ICU) (OR: 0.328, P < 0.001), and longer length of stay (LOS) (OR: 0.941, P < 0.001) were independently related to a lower probability of achieving clinical success. However, longer days of omadacycline use were independently associated with a higher probability of achieving clinical success (OR: 1.121, P < 0.001). Regarding adverse events, the incidence of coagulation disorders, acute kidney injury, liver injury, and gastrointestinal reaction was 10.5%, 9.9%, 6.2%, and 5.3%, respectively.ConclusionOmadacycline possesses favorable efficacy and safety for the treatment of infectious diseases. Baseline age, malignancy history, renal function, mechanical ventilation, ICU, LOS, and omadacycline use duration are strong predictors of clinical success.